2017
DOI: 10.1007/s13760-017-0775-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk factors for vitamin D levels in medium- and long-term use of antiepileptic drugs in childhood

Abstract: Antiepileptic drugs (AED) have potential side effects through vitamin-D. Prevalence of vitamin D insufficiency and potential risk factors for the longitudinal changes of vitamin D levels compared to its baseline levels under AED treatment were investigated in this study. This retrospective study includes patients whose AED therapy were started in only autumn months, between 2000 and 2014. Detailed assessment of neurologic diagnosis and brain MRI findings, ambulatory status, types and durations of AED treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
1
10
2
Order By: Relevance
“…This study established that vitamin D deficiency or insufficiency is common in children with epilepsy on ASMs in this region of sub-Saharan Africa, occurring in 60.3% of the study group. Similar results were found in other studies undertaken in Australia, USA, Denmark, Spain, Turkey, Israel, Iran, Egypt, and Korea where the prevalence of vitamin D deficiency or insufficiency in children with epilepsy ranged between 50-66% [20][21][22][23][24]26,32,34,37]. As demonstrated since vitamin D deficiency is common in children with epilepsy, where there is capacity, all patients on ASMs should be investigated for vitamin D deficiency and supplemented accordingly.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This study established that vitamin D deficiency or insufficiency is common in children with epilepsy on ASMs in this region of sub-Saharan Africa, occurring in 60.3% of the study group. Similar results were found in other studies undertaken in Australia, USA, Denmark, Spain, Turkey, Israel, Iran, Egypt, and Korea where the prevalence of vitamin D deficiency or insufficiency in children with epilepsy ranged between 50-66% [20][21][22][23][24]26,32,34,37]. As demonstrated since vitamin D deficiency is common in children with epilepsy, where there is capacity, all patients on ASMs should be investigated for vitamin D deficiency and supplemented accordingly.…”
Section: Discussionsupporting
confidence: 85%
“…This is the first study to report that children on enzyme-inducing ASMs have lower levels of 25(OH)D 2 and 24,25(OH) 2 D 3 levels probably as result of increased destruction of vitamin D. The median duration of ASMs was five and a half years so the group had established time period of epilepsy and prolonged time period of prescribed ASMs. However, this study did not show difference in the number of ASMs used between children with vitamin D deficiency and those without, compared to other studies which have shown polytherapy to be associated with lower vitamin D levels [19,21,22,27,28,40,42,43]. Our cohort was recruited from a tertiary center which manages a greater proportion of children with severe forms of epilepsy requiring multiple ASMs.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations